Zabawa we wczesnej terapii logopedycznej u dzieci z zespołem Downa - Kaptur, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The concept of early speech therapy by a team of therapists of different specializations, including a speech and language pathologist, assumes a holistic approach to an infant’s development. Children with Down syndrome require the help of a speech and language pathologist since the first day of their lives. The article describes activating the child’s speech by incorporating games into the therapy.